Gambaran Karakteristik Pekerja dan Kejadian Kecacingan di Tambang Intan Tradisional Kota Banjarbaru - Yohanes Joko Supriyadi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract : Characteristics Description Of Workers And Events In Mine Intantradisional Helminthiases Banjarbaru City. Description of Characteristics and Genesis Helminthiases Workers in Traditional Diamond Mine Banjarbaru . The disease is common worm infection in the community and are often considered harmless. This condition if left unchecked will mengakibatkatkan malnutrition, decreased endurance and work productivity , symptoms of chronic worm infection is the occurrence of anemia. One of the biggest potential danger from mining activities are biological factors that worm infection . This study aims to describe the characteristics of workers and events kecacingandi traditional diamond mines in the district Cempaka Banjarbaru . This research is descriptive . The study population was all workers in the traditional diamond mine in the village of Desa Sungai Tiung, Kelurahan Cempaka, Banjarbaru city with a sample size of 60 people . The variables studied were the characteristics of workers and the incidence of intestinal worms . The results of the study illustrates the proportion of 46-50 year age mostly ( 25 % ) , the majority of elementary education level ( 73.3 % ) , long working mostly 6 hours ( 50 % ) , most of the work period 16-20 years ( 28 , 3 % ) , long break 1-1.5 hours ( 100 % ) , the largest work activities that pelinggangan fine sand ( 45 % ) , normal nutritional status ( 46.7 % ) , lack of knowledge level ( 63.3 % ) ; using PPE at work ( 63.3 % ) ; Good personal hygiene ( 51.7 % ) , bowel habits are not eligible ( 60.0 % ) and worm infection ( 33.3 % ) . Expected workers use personal protective equipment , health checked regularly , get used to living a clean and healthy behavior and positive special miners infected worms always take medicine and health centers as well as familiarize dengaan consultation defecate in the toilet / latrine healthy . Keywords : Characteristics of tradisional miners, worm infection